2010
DOI: 10.1007/s13280-009-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

A North Sea and Baltic Sea Model Ensemble Eutrophication Assessment

Abstract: A method to combine observations and an ensemble of ecological models is suggested to produce a eutrophication assessment. Using threshold values and methodology from the Oslo and Paris Commissions (OSPAR) and the Helsinki Commission (HELCOM), four models are combined to assess eutrophication for the Baltic and North Seas for the year 2006. The assessment indicates that the entire southeastern part of the North Sea, the Kattegat, the Danish Straits, the Gulf of Finland, and the Gulf of Riga as well as parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…In 2007, to reduce eutrophication of the Baltic Sea, all nine surrounding countries have agreed upon reduction targets given in the BSAP (Table 7). The plan was concluded that inputs to the Baltic Sea should be reduced by about 18% (115,000 t) of N and 42% (15,000 t) of P, respectively (BSAP, 2007;Almroth and Skogen, 2010;Hong et al, 2012). Overall inputs of nutrients have decreased since the inception of the BSAP (2007), by 9% for TN, and 10% for TP, compared to the BSAP baseline years 1997-2003.…”
Section: How To Reverse and Prevent The Degradation Of The Baltic Sea?mentioning
confidence: 99%
“…In 2007, to reduce eutrophication of the Baltic Sea, all nine surrounding countries have agreed upon reduction targets given in the BSAP (Table 7). The plan was concluded that inputs to the Baltic Sea should be reduced by about 18% (115,000 t) of N and 42% (15,000 t) of P, respectively (BSAP, 2007;Almroth and Skogen, 2010;Hong et al, 2012). Overall inputs of nutrients have decreased since the inception of the BSAP (2007), by 9% for TN, and 10% for TP, compared to the BSAP baseline years 1997-2003.…”
Section: How To Reverse and Prevent The Degradation Of The Baltic Sea?mentioning
confidence: 99%
“…Coastal areas of the south-eastern North Sea and large parts of the Baltic Sea, including the Kattegat, have been heavily eutrophicated for decades (Almroth andSkogen 2010, Gustafsson et al 2012). This has caused substantial compositional shifts in the macroalgal communities, with a general decline in large, perennial species, and an increase in opportunistic species (Schramm 1996(Schramm , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Although same "scores" do not always mean same level of model performances, the statistical measures provide a possibility to inter-compare skills across models applied in different regions. In comparison with other models in the Baltic Sea and nearby regions, the overall skills of this model system are at the same level of these types of models (Edelvang et al, 2005;Lacroix et al, 2007;Lewis andAllen, 2009, Almroth andSkogen, 2010).…”
Section: Model Validitymentioning
confidence: 98%